2014
DOI: 10.1103/physrevb.90.125112
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast dynamics of finite Hubbard clusters: A stochastic mean-field approach

Abstract: Finite lattice models are a prototype for strongly correlated quantum systems and capture essential properties of condensed matter systems. With the dramatic progress in ultracold atoms in optical lattices, finite fermionic Hubbard systems have become directly accessible in experiments, including their ultrafast dynamics far from equilibrium. Here, we present a theoretical approach that is able to treat these dynamics in any dimension and fully includes inhomogeneity effects. The method consists in stochastic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 33 publications
(37 reference statements)
5
54
1
Order By: Relevance
“…In nuclear physics this approach, called stochastic mean field [36], has been originally introduced such that initial fluctuations in collective space are reproduced through arXiv:1609.01424v2 [nucl-th] 21 Mar 2017 fluctuations of the initial one-body density. In a series of works, it was shown that it surprisingly well accounts for correlations beyond mean-field [37][38][39] while treating properly the dynamic close to a spontaneous symmetry breaking [38]. It is also able to include approximately many-body correlation to all orders by connecting the evolution to the BBGKY hierarchy [40].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In nuclear physics this approach, called stochastic mean field [36], has been originally introduced such that initial fluctuations in collective space are reproduced through arXiv:1609.01424v2 [nucl-th] 21 Mar 2017 fluctuations of the initial one-body density. In a series of works, it was shown that it surprisingly well accounts for correlations beyond mean-field [37][38][39] while treating properly the dynamic close to a spontaneous symmetry breaking [38]. It is also able to include approximately many-body correlation to all orders by connecting the evolution to the BBGKY hierarchy [40].…”
mentioning
confidence: 99%
“…[41]. Although the stochastic mean-field technique was applied to simple models [37][38][39]42] or to obtain expressions of transport coefficients [40,[43][44][45][46], we present here the first application to a realistic physical phenomena where the phasespace sampling is explicitly made.…”
mentioning
confidence: 99%
“…[14] to describe small superfluid systems and shown to be competitive with most recent NEGF theories applied to lattice systems in Ref. [15].…”
Section: Introductionmentioning
confidence: 99%
“…This has been misleadingly interpreted in Refs. [13][14][15] as a generic defect of SMF. These two figures clearly demonstrate that this overdamping can disappear simply by changing the initial distribution.…”
Section: B Initial Phase-space Associated To Coherent and Correlatedmentioning
confidence: 99%
“…The lowest order for the correlation selfenergy is given by the second order Born (2B) approximation. The relaxation dynamics of finite Hubbard clusters in nonequilibrium revealed [24,27,30] that the Born approximation works well for weak coupling, U 0.1. For larger coupling, the simulations have a limited time range where they are valid that shrinks as U −1 .…”
Section: Nonequilibrium Green Functions T-matrix Approximationmentioning
confidence: 99%